Microsporum canis infection mimics pemphigus erythematosus - Hiroo Amano; Chikako Kishi; Yoko Yokoyama; Akira Shimizu; Kazushi Anzawa; Takashi Mochizuki; Osamu Ishikawa (Wolters Kluwer Medknow Publications, 2013)
We report a 55-year-old Japanese woman with a two-month history of multiple pruritic erythema and erosion on her face and neck. Based on the clinical appearance, we initially diagnosed her as having pemphigus erythematosus. However, the results of a histopathological examination and a direct immunofluorescence study did not support the initial diagnosis. Additionally, anti-desmoglein 1 and 3 antibodies were all negative. Subsequently, a microscopic examination of scales revealed filaments of fungi and a fungal culture was negative for macroconidium. Using molecular biology techniques, we identified the fungus as Microsporum canis, which causes a zoonotic infection. The immune reaction to the fungi could be drastic and therefore, the eruption sometimes displays atypical clinical manifestations.